Ancestrally Reconstructed von Willebrand Factor Reveals Evidence for Trench Warfare Coevolution between Opossums and Pit Vipers. (20th June 2022) - Drabeck, Danielle H; Rucavado, Alexandra; Hingst-Zaher, Erika; Dean, Antony; Jansa, Sharon A
Abstract: Opossums in the tribe Didelphini are resistant to pit viper venoms and are hypothesized to be coevolving with venomous snakes. Specifically, a protein involved in blood clotting (von Willebrand factor [vWF] which is targeted by snake venom C-type lectins [CTLs]) has been found to undergo rapid adaptive evolution in Didelphini. Several unique amino acid changes in vWF could explain their resistance; however, experimental evidence that these changes disrupt binding to venom CTLs was lacking. Furthermore, without explicit testing of ancestral phenotypes to reveal the mode of evolution, the assertion that this system represents an example of coevolution rather than noncoevolutionary adaptation remains unsupported. Using expressed vWF proteins and purified venom CTLs, we quantified binding affinity for vWF proteins from all resistant taxa, their venom-sensitive relatives, and their ancestors. We show that CTL-resistant vWF is present in opossums outside clade Didelphini and likely across a wider swath of opossums (family Didelphidae) than previously thought. Ancestral reconstruction and in vitro testing of vWF phenotypes in a clade of rapidly evolving opossums reveal a pattern consistent with trench warfare coevolution between opossums and their venomous snake prey.